The Digital Learning Guidebook as a New Breakthrough in Improving Students' Reading and Writing Skills - Yosoa, Valentina Dewi; Widiana, I Wayan; Jayanta, I Nyoman Laba (Journal of Education Technology, 2024)
The close relationship between reading and writing literacy allows students to obtain information, increase knowledge, and express ideas in writing. However, the reality in the field shows that literacy literacy in reading and writing is still lacking, mainly due to the lack of specific learning guides, limited use of literacy materials, and students' low interest in reading. Therefore, there needs to be a literacy guide that is clearer and more appropriate to student needs. This development research uses a 4-D model with the aim of developing a digital-based learning guidebook to improve the reading and writing skills of second grade elementary school students. The subjects involved in this research were three experts, namely content experts, language experts and design experts. The method used in data collection is a questionnaire. Meanwhile, data analysis was carried out using qualitative descriptive analysis techniques and quantitative descriptive analysis. The research results show that the book developed meets the criteria for feasibility, practicality and effectiveness. Innovative digital-based learning guidebooks have been proven to be used as a potential solution to reading and writing literacy challenges. Therefore, this research has implications for increasing reading and writing literacy learning that is fun for students and can prevent boredom during learning.